Multiple Event Study of Covid-19 Wave In Indonesia - Gessal, Zevania E.V.; Kotambunan, Eunike R.J.; Sumanti, Elvis Ronald (SAFE-Network, 2024)
The Covid-19 pandemic not only affects public health but also strongly affects economic health throughout the world, more specifically in Indonesia. This study aims to see whether there are differences in the reactions of investors when there is a surge in the first wave, second wave and third wave in determining investment decisions. This research is a quantitative study using the event study method to see investor reactions from the covid-19 wave surge that affects daily stock price index movements in Indonesia. The population used in this study is stock prices in Indonesia from dates where there are spikes and decreases in Covid-19 cases. The research sample uses several Indonesian Stock Indexes. From the research that has been done, the resulting data shows that investors in Indonesia do not react significantly to the peak and valley waves of Covid-19. Only on some specific dates there is a significant change in reaction related to the Covid-19 wave. This explains that in Indonesia, information about the Covid-19 wave does not have a significant influence on the reaction of investors in determining their investment decisions, they are more focused on several other factors.